2003
DOI: 10.1086/367675
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Infection of Dendritic Cells: Balance among Activation, Inhibition, and Immunity

Abstract: Several lines of evidence suggest that dendritic cells (DCs),Herpes simplex virus (HSV) belongs to the Herpesviridiae family, which have the characteristic ability to establish latency after primary infection, and thus to persist in the human host for life. For a virus to do so, it must be able to avoid immune eradication both after primary infection and after subsequent reactivation.Although the importance of innate immunity in HSV infection has been well characterized [1], it is the degree of adaptive immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
129
1
1

Year Published

2004
2004
2006
2006

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(141 citation statements)
references
References 56 publications
10
129
1
1
Order By: Relevance
“…This is in accordance with a recent report showing that roughly 80% of immature DC stain positive for HSV antigens after infection with HSV [15]. Thus, HSV efficiently infects immature DC as also shown by previous studies [10,11,[13][14][15]. Using annexin V staining and TUNEL assay, we observed that a significant percentage of immature DC undergo apoptosis after HSV infection.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is in accordance with a recent report showing that roughly 80% of immature DC stain positive for HSV antigens after infection with HSV [15]. Thus, HSV efficiently infects immature DC as also shown by previous studies [10,11,[13][14][15]. Using annexin V staining and TUNEL assay, we observed that a significant percentage of immature DC undergo apoptosis after HSV infection.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, it has been shown that CD95 ligation can activate DC [21]. Thus c-FLIP L might be involved in maturation of DC and its down-regulation could contribute to the activation block observed after HSV infection [11,[13][14][15]. In accordance with this idea we observed that LPS, a strong stimulus of DC activation, did not abrogate HSVinduced down-regulation of c-FLIP L in immature DC.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Most studies demonstrated that HSV-1 infects immature DCs efficiently, resulting in effects such as incomplete maturation, inadequate induction of T-cell responses or delayed apoptosis (Björck, 2004;Galvan & Roizman, 1998;Mikloska et al, 2001;Müller et al, 2004;Pollara et al, 2003). In addition, when immature DCs were infected efficiently with HSV-1 (>90 % EGFP-positive cells), we saw a dramatic effect on maturation, in the form of reduced CCR7 and CXCR4 expression, and reduced chemokine-mediated migration was observed.…”
Section: Discussionmentioning
confidence: 99%